2020
DOI: 10.3390/biom10030361
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53-Associated Molecular Mechanisms of ROS Regulation in Cancer Cells

Abstract: The TP53 tumor suppressor gene is the most frequently altered gene in tumors and an increasing number of studies highlight that mutant p53 proteins can acquire oncogenic properties, referred to as gain-of-function (GOF). Reactive oxygen species (ROS) play critical roles as intracellular messengers, regulating numerous signaling pathways linked to metabolism and cell growth. Tumor cells frequently display higher ROS levels compared to healthy cells as a result of their increased metabolism as well as serving as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 170 publications
(225 reference statements)
4
70
0
Order By: Relevance
“…Interestingly, mTOR may be also activated by cytokines [74,75] and, as UPR has a key role in regulating the release of these molecules, UPR signaling could contribute to mTOR activation also by increasing the production of these cytokines. Of note, mutp53, in contrast to its wild-type counterpart, may support mTOR signaling, sustaining an oxidative environment that leads to uncontrolled cancer cell proliferation [76]. Indeed, it has been recently reported that hotspot mutp53 promotes the phosphorylation of the mTORC1 targets S6K1 and 4EBP1 in both colon and non-small carcinoma cells [77].…”
Section: Cross Talk Between Mtor Upr Autophagy and Mutp53mentioning
confidence: 99%
“…Interestingly, mTOR may be also activated by cytokines [74,75] and, as UPR has a key role in regulating the release of these molecules, UPR signaling could contribute to mTOR activation also by increasing the production of these cytokines. Of note, mutp53, in contrast to its wild-type counterpart, may support mTOR signaling, sustaining an oxidative environment that leads to uncontrolled cancer cell proliferation [76]. Indeed, it has been recently reported that hotspot mutp53 promotes the phosphorylation of the mTORC1 targets S6K1 and 4EBP1 in both colon and non-small carcinoma cells [77].…”
Section: Cross Talk Between Mtor Upr Autophagy and Mutp53mentioning
confidence: 99%
“…However, mutant p53-driven ROS accumulation was also shown to enhance cell sensitivity to H 2 O 2 treatment. It was then speculated that mutant p53-bearing cancer cells could be significantly more sensitive to prooxidant drugs [82]. In conclusion, the final effect of p53 activation seems to be dependent on the cell type, p53 isoform, level of p53 activity, and its location within the cell and can promote cell proliferation, migration, further genotoxic damage, senescence, or cell death.…”
mentioning
confidence: 99%
“…Through increasing the expression of antioxidant genes, such as glutathione peroxidase and aldehyde dehydrogenase 4, p53 can prevent excessive ROS production that could compromise genome integrity [32,33]. In contrast with the wild-type, mutant p53 proteins sustain ROS formation and promote tumor progression by regulating Nrf2 and PGC-1α target genes [34].…”
Section: Discussionmentioning
confidence: 99%